Efficacy and safety of apixaban for primary prevention of thromboembolism in patients with cancer and a central venous catheter: A subgroup analysis of the AVERT Trial. Issue 216 (August 2022) - Brandt, Willem; Brown, Cameron; Wang, Tzu-Fei; Tagalakis, Vicky; Shivakumar, Sudeep; Ciuffini, Leonardo A.; Mallick, Ranjeeta; Wells, Phil S.; Carrier, Marc
Abstract: Introduction: Central venous catheters (CVC) are associated with an increased risk of venous thromboembolism (VTE) in patients with cancer. Primary thromboprophylaxis using a direct oral anticoagulant decreases the risk of VTE in intermediate-to-high risk ambulatory cancer patients. We assessed the efficacy and safety of thromboprophylaxis with apixaban in the subpopulation of patients with cancer and a CVC in the AVERT trial. Methods: The AVERT study was a randomized, placebo-controlled, double-blind clinical trial assessing the efficacy and safety of apixaban for primary thromboprophylaxis in patients with cancer initiating chemotherapy who were at intermediate to high risk of VTE. The primary efficacy outcome was objectively confirmed VTE within 180 days of randomization and the primary safety outcome was major bleeding. The hazard ratios (HRs) were calculated using a Cox regression model controlling for age, gender, and center. Results: A total of 217 patients had a CVC and were included in the subgroup analyses with 126 and 91 patients receiving apixaban or placebo, respectively. VTE occurred in 6 (4.8%) patients in the apixaban group and 17 (18.7%) patients in the placebo group (HR 0.26; 95% CI, 0.14–0.47; p < 0.0001). Major bleeding occurred in 2 (1.6%) patients in the apixaban group and 2 (2.2%) patients in the placebo group (HR 0.69; 95% CI, 0.20–2.35; p = 0.556). Conclusions: Primary thromboprophylaxis with apixaban in patients with cancer and a CVC was associated with a reduced risk of VTE in the AVERT study population, without an increased risk of bleeding. (Funded by the CIHR and Bristol-Myers Squibb-Pfizer Alliance; NCT02048865 ). Highlights: Central venous catheters increase the risk of venous thromboembolism in cancer patients. Routine thromboprophylaxis is currently not recommended for these patients. We sought to assess the efficacy and safety of thromboprophylaxis with apixaban. Apixaban is associated with lower risk of VTE without an increased the risk of bleeding.